Comparisons of ensiled maize, sorghum and pearl millet forages fed to sheep - Vinutha, K.S.; Khan, A.A.; Prakasham, R.S.; Srinivas Raol, P.; Ravi, D.; Prasad, Kodukula V.S.V.; Ramana Reddy, Y.; Blümmel, Michael (2016)
Water-use efficient sorghum (7) and pearl millet (5) forages were compared with reference maize forage as silage tested with Nellore Brown sheep. Mean silage organic matter intake was 352, 297 and 137g!d in maize, sorghum and pearl millet silage, respectively Current pearl millet forage cultivars do not match maize forage in terms of fodder quality Of the 7 sorghum cultivars several were on par with maize though the cultivar dependent variation in intake was huge (254 to 343g!d). Anti-nutritive factors associated with sorghum like dhurrin were undetectable in the silages, although present in the fresh forage. A routine laboratory trait does not seem to describe sorghum and pearl millet forages adequately More research is required to understand the true nutritional potential of sorghum and in particular pearl millet forages. Dissemination of these forages based on only biomass yield should be discouraged.